2015
DOI: 10.1007/s10803-015-2602-7
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Emotional Distress in Autism Spectrum Disorder: Foundations and Considerations for Future Research

Abstract: Autism spectrum disorder (ASD) is often associated with emotional distress and psychiatric comorbidities. Atypical emotion regulation (ER) may underlie these accompanying features. This special issue of the Journal of Autism and Developmental Disorders presents a series of mechanistic and applied papers on ER and emotional experiences in ASD. Important concepts for future research are discussed, including how to conceptualize emotion dysregulation in ASD, the importance of capturing variability in emotion dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 14 publications
3
54
0
2
Order By: Relevance
“…As a result, the current study provides initial support for the continued relevance of the CARS in the diagnosis of ASD in two year olds using the DSM-5. Further, the current study’s finding of an additional Emotional Reactivity factor supports the growing body of literature highlighting the importance of understanding emotion regulation and emotional distress in individuals with ASD (e.g., Mazefsky 2015). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As a result, the current study provides initial support for the continued relevance of the CARS in the diagnosis of ASD in two year olds using the DSM-5. Further, the current study’s finding of an additional Emotional Reactivity factor supports the growing body of literature highlighting the importance of understanding emotion regulation and emotional distress in individuals with ASD (e.g., Mazefsky 2015). …”
Section: Discussionsupporting
confidence: 83%
“…This is notable given that while stereotyped behaviors are included as a core symptom domain in DSM-IV-TR and DSM-5, emotional reactivity is not. Emotion regulation difficulties are certainly not specific to ASD, and therefore, likely would not be a meaningful core symptom domain; however, understanding difficulties in emotion regulation in this group may prove helpful in creating meaningful subgroups in research studies (Mazesfky 2015), and in planning appropriate intervention targets. Given that the gold standard diagnostic measures, the ADOS and ADI-R, do not emphasize this domain of functioning, the CARS could provide useful unique information in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that care-givers' relationships and attachment are important protective/resilience factor of depressive symptoms in adolescents with high functioning ASD. Given that adolescents with high functioning ASD are biologically vulnerable to depressive symptoms (Case-Smith et al, 2015;Mazefsky, 2015;Pitskel et al, 2014;Minke et al, 2014), the present study supports that building strong relationship with significant adult caregiver could be a feasible way of moderating biological depressive vulnerability in adolescents with high functioning ASD. Through physical and psychological supports, caregivers can help adolescents with high functioning ASD navigate their social-emotional and functional situations that could ordinarily constitute stress to such individual (Mazefsky et al, 2016;Minke et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…As noted, self‐regulation is a broad construct encompassing cognitive and emotion aspects of self‐regulation [Mick et al, ] and a large body of research in ASD indicates significant impairment across all aspects of self‐regulation including executive functioning [Hill, ], effortful control [Adamek, Nichols, Tetenbaum, Ponzio, & Carr, ; De Pauw, Mervielde, Van Leeuwen, & De Clercq, ; Faja & Dawson, ], and emotion regulation [Berkovits, Eisenhower, & Blacher, ; Cai, Richdale, Foley, Trollor, & Uljarević, ; Cai, Richdale, Dissanayake, & Uljarević, ; Konstantareas & Stewart, ; Mazefsky et al, ; Mazefsky, ; Nuske et al, ; Pitskel, Bolling, Kaiser, Pelphrey, & Crowley, ; Richey et al, ; Samson et al, ; for comprehensive overviews, please see Cai et al, under review and Mazefsky & White, ]. Importantly, impairments in cognitive aspects of self‐regulation have been found that are associated with a range of negative outcomes in ASD, in terms of both core and associated ASD symptomatology [Hollocks et al, ; Leekam, Prior, & Uljarević, ; Macari, Koller, Campbell, & Chawarska, ; Uljarević, Richdale, Evans, Cai, & Leekam, 2017; Wallace et al, ].…”
Section: Introductionmentioning
confidence: 99%